2009
DOI: 10.1590/s0104-42302009000500026
|View full text |Cite
|
Sign up to set email alerts
|

Perfurações não detectadas de luvas em procedimentos de urgência

Abstract: We concluded that the incidence of punctures in gloves during surgical procedures was high, and occurred mostly with surgeons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0
6

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 27 publications
2
3
0
6
Order By: Relevance
“…In addition, scrub nurses sustained the second highest rate of glove perforation during elective procedures. These findings are in agreement with the literature, as various studies have shown that surgeons and scrub nurses have the highest rates of glove perforations [7, 8, 20]. One possible explanation is that compared to first, second, and third assists, the main surgeons, are the ones using instruments directly and for longer durations in procedures with increased risks for perforations.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In addition, scrub nurses sustained the second highest rate of glove perforation during elective procedures. These findings are in agreement with the literature, as various studies have shown that surgeons and scrub nurses have the highest rates of glove perforations [7, 8, 20]. One possible explanation is that compared to first, second, and third assists, the main surgeons, are the ones using instruments directly and for longer durations in procedures with increased risks for perforations.…”
Section: Discussionsupporting
confidence: 91%
“…In addition, studies that have compared the rate of perforation among elective and emergency surgeries have shown that perforation to be higher in emergency surgical procedures [7, 8]. In addition, one of the major challenges encountered during surgical glove perforation is that the operating staff is not aware of the perforation until the procedure is complete, sometimes in as high as 70% of the incidences [1].…”
Section: Introductionmentioning
confidence: 99%
“…The study glove area that suffered the greatest number of perforations was the finger area (60.7%), a finding corroborated by Xavier et al 4 , Soldá et al 11 , Oliveira Neto et al 8 , and Leal et al 10 .…”
Section: Discussionsupporting
confidence: 58%
“…oral surgery, endodontic treatment, prosthodontics treatment, periodontics treatment & orthodontic treatment. [12][13][14] A system for identifying intra-operative glove perforations tracking procedure is beneficial. 15 A research had been done to investi gate glove perforation indication system & the results with double gloving in surgery of maxillofacial trauma, which concluded reduced rate of inner gloves as compare to outer gloves.…”
Section: Discussionmentioning
confidence: 99%